Energy, Exergy, and Economic Analyses and Optimization of Solar Organic Rankine Cycle with Multi-objective Particle Swarm Algorithm - Beiranvand, A.; Ehyaei, M. A.; Ahmadi, A.; Silveira, Jose Luz [UNESP] (Shahrood Univ Technology, 2021)
The high potential of solar energy in Iran as well as the problem of air pollution makes it increasingly inevitable that solar energy is used. In this work, the solar-powered organic Rankine cycle (ORC) is investigated. A solar-type collector is a flat plate collector. The energy, exergy, and economic analyses of the hybrid system with the MOPSO algorithm are carried out for Tehran, the capital of Iran. The working fluid of the solar collector is assumed to be water, and the working fluid of ORC is R123. The MATLAB software is used for the simulation, and to compute the R123 fluid properties, the Refprop software is used. The exergy investigation shows that the most exergy destruction is related to the evaporator. Two objective functions consisting of the exergy efficiency and the price of electricity are considered. The decision variables for this optimization are considered as the number of solar collector panels and the pumps, the turbine isentropic efficiency, and the pressures of the condenser and the evaporator. The Pareto diagram shows that the exergy efficiency of the system can vary in the range of 7.5-10.5 %, and the price of the produced electricity can vary in the range of 0.2-0.26 $/kWh.
Keywords: Exergy; Organic Rankine cycle; Flat collector; Energy; Economic; Solar